2001
DOI: 10.1042/bj3580217
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum Ca2+-ATPase pump is up-regulated in calcium-transporting dental enamel cells: a non-housekeeping role for SERCA2b

Abstract: Dental enamel-forming cells face a major challenge to avoid the cytotoxic effects of excess calcium. We have characterized sarcoplasmic/endoplasmic reticulum calcium-ATPase pumps (SERCA) in rat enamel cells to address the proposal that non-mitochondrial calcium stores play a dominant role in transcellular calcium transport. A single major isoform, SERCA2b, was detected during the protein-secretory and calcium-transport stages of enamel formation using reverse-transcriptase PCR, cDNA cloning, Northern analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
7
22
1
Order By: Relevance
“…During PDGF-induced SMC proliferation, SERCA2a expression was up-regulated while SERCA2b expression was unchanged (6). However, the concept of a exclusive housekeeping role of SERCA2b has recently been questioned as it has become clear that SERCA2b could be the only SERCA isoform expressed by highly differentiated cells (31). Recent results from our laboratory support this new standpoint: the thyrocyte is similar to enamel cells in that it is a highly differentiated cell expressing almost exclusively SERCA2b (20).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…During PDGF-induced SMC proliferation, SERCA2a expression was up-regulated while SERCA2b expression was unchanged (6). However, the concept of a exclusive housekeeping role of SERCA2b has recently been questioned as it has become clear that SERCA2b could be the only SERCA isoform expressed by highly differentiated cells (31). Recent results from our laboratory support this new standpoint: the thyrocyte is similar to enamel cells in that it is a highly differentiated cell expressing almost exclusively SERCA2b (20).…”
Section: Discussionsupporting
confidence: 66%
“…Total RNA (20 mg) was analyzed by electrophoresis on a 1.2% formaldehyde agarose gel and blotted onto nitrocellulose membranes (BioRad, Hercules, CA, USA). Filters were washed twice in 10 ml 2 £ SSPE (0.3 M NaCl, 0.02 M NaH 2 PO 4 and 0.002 M EDTA), incubated for 5 h at 42 8C in 10 ml pre-hybridization buffer (50% formamide, 5 £ SSPE, 2 £ Denhardt's, 0.2% SDS and 100 mg/ml sonicated denaturated salmon sperm DNA) and then for 16 h in 10 ml of the same buffer with 1 £ 10 7 c.p.m./ml of a [ 32 P]-dATPlabeled specific probe encompassing bp 2074-2590 of rat SERCA2b cDNA (31). After the hybridization step, filters were washed twice at room temperature in 10 ml 2 £ SSPE and 0.2% SDS and once at 42 8C in the same washing buffer.…”
Section: Rna Extraction and Northern Blot Experimentsmentioning
confidence: 99%
“…Here, it is shown that SERCA 2b activity is stimulated by P2-purinergic agonists through the PLC-PKC pathway. These results strengthen the concept that SERCA 2b, in highly differentiated cells, such as thyroid (Pacifico et al 2003) or enamel cells (Franklin et al 2001), is regulated by various signal transduction pathways. This new standpoint extends our understanding of SERCA 2b function, considered until recently housekeeping at variance with that of SERCA 3 that varies with differentiation in several systems (Papp et al 1993, Gelebart et al 2002.…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, the 3-fold increased transport rate at maturation, quantified here for the first time (Fig. 3), closely matches the up-regulation of ER/Ca 2ϩ store machinery (12,14) and associated capacity for sequestering 45 Ca. 3 Collectively, the results of this study warrant further investigation of the calcium transcytosis paradigm in enamel cells.…”
Section: Discussionmentioning
confidence: 81%
“…Unexpectedly, however, proteome analysis revealed that calbindin 28kDa was down-regulated during maturation, whereas calcium-handling proteins from the endoplasmic reticulum (ER/Ca 2ϩ stores) 1 were elevated in parallel with calcium transport. These and other findings led us to postulate a "calcium transcytosis" mechanism whereby the ER serves as a transcellular pipeline for calcium (1,(12)(13)(14). Null mutant mice completely lacking calbindin 28kDa (15) constitute a powerful tool to pursue this stimulating possibility further.…”
mentioning
confidence: 99%